Mental health literacy intervention to reduce stigma toward mental health symptoms and disorders in women rugby players: A feasibility study - Oftadeh-Moghadam, S.; Weston, N.; Gorczynski, P. (The Sport Psychologist, 2023)
This feasibility study aimed to evaluate the effectiveness of an educational intervention on stigma toward mental health symptoms and disorders, mental health literacy, and help-seeking intentions among U.K. semielite women rugby players. Seven semielite women rugby players participated. An A-B-A single-case experimental research design was used to assess stigma toward mental health symptoms and disorders, mental health literacy, and help-seeking intentions at baseline, intervention, and follow-up phases. The intervention was successful in enhancing the players` mental health literacy and reducing stigmatizing attitudes toward seeking professional psychological help. Acknowledging the study`s small sample size, the findings revealed that there is a need for scaffolding to support future developments, advancements, and maintenance of mental health support in women`s rugby. Practical implications of future findings from a larger-scale study may lead to policy reformation across the game to inform and improve systemic mental health support for women rugby players.